Device Closure in Congenital Heart Disease - Regmi, Shyam (Nepalese Heart Journal, 2006)
A device to plug holes in the heart without open-heart surgery has been available for a decade. James Lock, M.D., chief cardiologist at Children’s Hospital Boston, developed his clamshell occluder for that purpose and also developed the CardioSEAL StarFlex, a newer model of that device. The StarFlex allows for the umbrella device to center itself to plug larger holes.